One-Year Multicenter Randomised Controlled Trial Comparing OT Equator® and Locator Attachments to Retain an Early Loaded Implant Overdenture on Two Implants - Tallarico, Marco; Fiorillo, Luca; Montanari, Marco; Scrascia, Roberto; Cristache, Corina Marilena; Ferrari, Emiliano; Casucci, Alessio; Xhanari, Erta; Lupi, Saturnino Marco; Ieria, Irene; Baldoni, Edoardo; Rodriguez y Baena, Ruggero; et al. (International Journal of Biomaterials, 2023)
This investigation aimed to compare the effectiveness of the OT Equator® (Rhein, Bologna, Italy) and the Locator attachment systems used to retain early loaded implant-retained overdentures. This study was designed as a multicenter randomised controlled trial of parallel groups. After implant placement, the patients were randomised to receive OT Equator® attachments in the test group or Locator attachments in the control group. The outcome measures were implant and prosthetic success and survival rates, any biological and technical complication, marginal bone loss, patients’ satisfaction, and periodontal parameters. Overall, 42 patients were consecutively enrolled and treated. One implant was lost in the control group, while no implants were lost in the test group. No prostheses failed in both groups. Only a few complications were experienced in both groups. The main was represented by loss of retention of the attachments (retentive caps). The OT Equator® attachment showed statistically lower periodontal parameters. In conclusion, both attachment systems were suitable for overdenture implant retention.